Study on Energy Efficient Motion Planning for Industrial SCARA Robots by Particle Swarm Optimization - Liu, Ziang; Fujiwara, Tomofumi; Nishi, Tatsushi (Shisutemu Seigyo Jouhou Gakkai rombunshi, 2024)
Reducing energy consumption in factories is important to reduce global warming. The objective of this study is to realize an energy-efficient motion plan for a robot arm that minimizes energy consumption and motion completion time for a part of the motion in which the robot arm carries a workpiece placed on a conveyor belt from an initial position to a speciﬁc target position. We conducted simulations to optimally tune the PID control gain of the industrial robot by using particle swarm optimization (PSO) in minimizing the energy consumption and motion completion time. As a result, a motion plan was obtained that reduced energy consumption while maintaining speed by inertia. The generated energy-efficient motion plans were applied to an industrial SCARA robot with results comparable to simulation.